Entropy generation minimization in a channel flow: Application to different advection-diffusion processes and boundary conditions. (20th July 2020) - Avellaneda, J.M.; Bataille, F.; Toutant, A.; Flamant, G.
Highlights: Optimized velocity fields are found by minimizing entropy generation. Heat and mass transfer improvement is assessed. Flow regime transition occurrence is described and analyzed. Several advection-diffusion situations exhibit similar qualitative behaviors. Influence of boundary conditions is analyzed. Abstract: Heat and mass transfer enhancement in a convective flow is studied using a variational optimization technique. Entropy generation rate is minimized while allowing to vary the relative weight of the total viscous dissipation in the objective functional to determine optimized velocity and scalar field patterns. The resulting velocity, thermal and mass concentration fields are analyzed as well as the influence of boundary conditions. The relative improvement of the optimized solutions is assessed and heat transfer vs. mass diffusion results are compared. The optimization approach leads to improved entropy generation rates. The viscous dissipation weighting factor influences the entropy generation rates and the velocity and scalar field patterns. A transition between two levels of perturbation by comparison to non-optimized flows occurs at a critical value of the weighting factor that depends on the boundary conditions. The flow patterns obtained by variational optimization can be the basis for enhanced exchanger design.